2020
DOI: 10.1111/myc.13212
|View full text |Cite
|
Sign up to set email alerts
|

Invasive dermatophyte infection: A systematic review

Abstract: Dermatophyte infections usually present as various types of superficial cutaneous mycoses; on very rare occasions, dermatophytes enter deep into the dermis and cause invasive infections. In this study, we aimed to perform a systematic review of all reported invasive dermatophytosis cases over the past 20 years. We performed systematic searches in PubMed/Medline, EMBASE and Web of Science and identified 123 papers reporting 160 individual cases of invasive dermatophytosis between 2000 and 2020. Our study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 35 publications
0
43
0
3
Order By: Relevance
“…Invasive dermatophytosis is rare, affecting exclusively immunocompromised patients including those with advanced HIV infection or patients with anti-fungal immunodeficiency, always with concomitant superficial dermatophytosis. 10 However, there is no concomitant superficial dermatophytosis in our patient living with HIV. The dermatophyte may have been inoculated by trauma from the pet.…”
Section: Discussionmentioning
confidence: 63%
“…Invasive dermatophytosis is rare, affecting exclusively immunocompromised patients including those with advanced HIV infection or patients with anti-fungal immunodeficiency, always with concomitant superficial dermatophytosis. 10 However, there is no concomitant superficial dermatophytosis in our patient living with HIV. The dermatophyte may have been inoculated by trauma from the pet.…”
Section: Discussionmentioning
confidence: 63%
“…7 The duration of treatment is uncertain, ranging from 2.5 1 to 4 months 8 or until the lesions disappear 9 and up to lifelong treatment in patients with gene deficiency. 4 The reported average time after transplant for diagnosis is between 7.5 and 16 months. 6 In our case the diagnosis was made 17 years after transplantation.…”
Section: F I G U R E 1 Histological Examination Of the Skin Biopsy (A...mentioning
confidence: 99%
“…The occurrence of cutaneous dermatophytosis may also lead to invasive and deep infections. A systematic review of cases of deep dermatophytosis worldwide, from 2000 to 2020 [ 20 ], showed that half of the patients presented chronic cutaneous infections at the same anatomical site before invasive lesions. Predisposing factors included the use of immunosuppressants, solid organ transplantation, mutations in the CARD9 or STAT3 (signal transducer and activator of transcription 3) genes, diabetes, and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, T. rubrum was the most prevalent dermatophyte, isolated in 53.1% of invasive cases, followed by T. mentagrophytes , M. canis , T. tonsurans , T. interdigitale , and T. violaceum . Other dermatophytes associated with these invasive cases were Trichophyton schoenleinii , Trichophyton verrucosum , Nannizzia gypsea (formerly Microsporum gypseum ), Microsporum inferrugineum , M. audouinni , and Arthroderma gypseum [ 20 ].…”
Section: Introductionmentioning
confidence: 99%